Evaluación de dos dosis de Trichoderma harzianum C-3 y tres tipos de abonaduras orgánicas en el rendimiento del cultivo de Ray-grass (Lolium perenne L), cantón Montúfar, provincia del Carchi - Cerón Calderón, Edison Hernando (2015)
This work was done in the area of San Pedro de la Piartal parish, canton Montufar, Carchi province in order to assess the best dose of Trichoderma harzianum C-3 and type of organic abonadura in crop yield of ray- grass (Lolium perenne L.), combined with Trichoderma harzianum C-3 seven treatments combined with organic fertilizers (Caprinaza, pig droppings and Bovinaza) applied in two doses of 4 and 8 L / ha was investigated. The complete block design Random (RCBD) was used in factorial arrangement A x B + 1 with 7 treatments and three repetitions, for a total of 21 experimental units, the total area of the experiment was 540.00 m2, experimental plots 16.00 m2 with a useful area of 14.00 m2., Percentage of germination, plant height, root length, weight of green and dry matter and compositional analysis was evaluated. Data analysis of variance underwent and comparison of treatments he made with Fisher test 5%.The results determined that the cultivation of ryegrass, responded positively to the abonadura with caprinaza as components of plant height, green matter weight (PMV), dry matter weight (PMS) and percentage of germination doses C-3 T. harzianum application did not present any difference in the evaluated components but with the witness, the best combination to achieve the highest plant height, green matter weight (PMV), dry matter weight (PMS) and germination percentage is the application caprinaza more 4 and 8 L / ha of T. harzianum C-3 addition to bromatologic ally it could obtain higher percentage of protein, fat, and ash and higher net income of USD 27917.2 / ha in the production of DDEr it He obtained with the application of more caprinaza4 L / ha of T. harzianum C-3